Điều trị khối u ác tính tại gan bằng nút mạch vi cầu phóng xạ Y-90 - Khoa, Mai Trọng; Hà, Trần Đình; Phương, Phạm Cẩm; Thái, Phạm Văn; Thông, Phạm Minh; Hiền, Nguyễn Xuân; Lâm, Ngô Lê; Bình, Trần Hải; Thống, Trần Văn (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
AA